2004
DOI: 10.1007/s00125-004-1335-5
|View full text |Cite
|
Sign up to set email alerts
|

The EGIR-RISC STUDY (The European group for the study of insulin resistance: relationship between insulin sensitivity and cardiovascular disease risk): I. Methodology and Objectives

Abstract: This study will evaluate the importance of insulin resistance in the development of CVD and diabetes, and has implications for the development of prevention and treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
197
0
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(204 citation statements)
references
References 24 publications
1
197
0
6
Order By: Relevance
“…The study population is part of the prospective Relationship between Insulin Sensitivity and Cardiovascular risk (RISC) study cohort [12]. From 2002 to 2004, individuals were recruited in 19 centres in 14 European countries [12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population is part of the prospective Relationship between Insulin Sensitivity and Cardiovascular risk (RISC) study cohort [12]. From 2002 to 2004, individuals were recruited in 19 centres in 14 European countries [12].…”
Section: Methodsmentioning
confidence: 99%
“…From 2002 to 2004, individuals were recruited in 19 centres in 14 European countries [12]. They were screened initially to confirm excellent health and the absence of any regular drug intake that may affect insulin sensitivity, blood pressure, circulating lipids or glucose.…”
Section: Methodsmentioning
confidence: 99%
“…We next included these loci and those of the other four genes reported to alter beta cell function, CDKN2A/B (rs10811661), IGF2BP2 (rs4402960), SLC30A8 (rs13266634) and KCNJ11 (rs5219), in our model to test the effects of all seven variants. To do this we used the RISC cohort that comprises non-diabetic men and women of European ancestry from 19 centres across 13 different countries [14]. Volunteers were recruited as part of a long-term study of insulin sensitivity and cardiovascular disease and those with diabetes, hypertension or dyslipidaemia were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the confirmed type 2 diabetes variants have since been shown in population cohorts to alter beta cell function [7][8][9][10][11][12][13]. These studies include the RISC (Relationship between Insulin Sensitivity and Cardiovascular Disease) study [14], where we previously showed that CDKAL1 (rs10946398) and HHEX/IDE (rs1111875) loci were associated with altered beta cell function as measured by the 30 min insulin response and pancreatic beta cell glucose sensitivity derived from an OGTT [10]. The aim of this study was to test the cumulative effects of variants shown individually to alter beta cell function.…”
mentioning
confidence: 99%
“…The Relationship Between Insulin Sensitivity and Cardiovascular Disease Risk (RISC) study is a prospective, observational cohort study whose rationale and methodology have been published [14]. In brief, participants were recruited from the local population at 19 centres in 14 countries in Europe, according to the following inclusion criteria: men and women, age between 30-60 years and clinically healthy.…”
Section: Study Participantsmentioning
confidence: 99%